Serum bactericidal activity as indicator of innate immunity in pacu Piaractus mesopotamicus (Holmberg, 1887) - Biller-takahashi, J.d. [UNESP]; Takahashi, L.s. [UNESP]; Pilarski, F.; Sebastião, F.a.; Urbinati, E.c. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2013)
The immune system of teleost fish has mechanisms responsible for the defense against bacteria through protective proteins in several tissues. The protein action can be evaluated by serum bactericidal activity and this is an important tool to analyze the immune system. Pacu, Piaractus mesopotamicus, is one of the most important fish in national aquaculture. However there is a lack of studies on its immune responses. In order to standardize and assess the accuracy of the serum bactericidal activity assay, fish were briefly challenged with Aeromonas hydrophila and sampled one week after the challenge. The bacterial infection increased the concentration of protective proteins, resulting in a decrease of colony-forming unit values expressed as well as an enhanced serum bactericidal activity. The protocol showed a reliable assay, appropriate to determine the serum bactericidal activity of pacu in the present experimental conditions.

O sistema imune de peixes teleósteos tem mecanismos responsáveis pela defesa contra bactérias e atua através de proteínas presentes em diversos tecidos. A ação destas proteínas pode ser avaliada pela atividade bactericida do soro, sendo esta uma importante ferramenta para analisar o sistema imune. O pacu, Piaractus mesopotamicus, é um peixe nativo muito importante para aquicultura nacional, entretanto há pouco conhecimento sobre o funcionamento de seu sistema imune. Assim foi realizado experimento para padronizar e avaliar a eficiência do ensaio de atividade bactericida. Resumidamente, peixes foram desafiados por Aeromonas hydrophila e amostradas uma semana após o desafio. A infecção bacteriana promoveu um aumento na concentração de proteínas protetoras, resultando em diminuição dos valores de unidades formadoras de colônias ou expressos também como aumento da atividade bactericida do soro. O protocolo se mostrou confiável, sendo apropriado para determinar a atividade bactericida do soro de pacu nas condições experimentais.
Atividade bactericida do soro como indicador de imunidade inata de pacu Piaractus mesopotamicus (Holmberg, 1887)
Keywords: imunologia inata de peixes; metodologia; imunidade humoral; fish innate immunology; methodology; humoral immunity